Expert API for Early Detection of TB Disease with Forward Chaining and Certainty Factor Algorithms - Wirasbawa, Nicholas Dwiarto; Widjaja, Christian Teguh Prasetya; Wenji, Christian Imanuel; Hansun, Seng (Informatica, 2022)
Despite being a curable disease, Tuberculosis has become the leading cause of death of infectious disease prior to COVID-19. It has asymptomatic infections that are hard to detect for weeks or years. Although there have been many studies on Tuberculosis disease detection and prevention, very few of them discussing the creation of an expert system based on API. Hence, in this study we propose an Expert API that implements Forward Chaining and Certainty Factor algorithms for the task of Tuberculosis early detection. The evaluation of the proposed system was carried out using several testing methods and in-depth interview with medical experts. We got a satisfactory result for this study.